Історія меліоративного ґрунтознавства в Угорщині з харківським забарвленням - Вергунов, В.А. (Питання історії науки і техніки, 2007)
В статье рассматриваются проблемы становления и развития мелиоративного
почвоведения в Венгрии через творческое наследие Самуэля Тешшедыка до академика
Яноша Домбовари. Делается периодизация научно-организационной структуры «тешшедиковского» почвоведения. In this article the problems of formation and development of land-reclamation soil science
in Hungary through the creative heritage of its founder Samuel Tesheduk and academician
UAAS Yanosh Dombovary. The division into periods of scientifically organizational
structure of “tesheduk’s” soil science.